The Syntactic Anatomy of the Idāfah Construction: A Contrastive Analysis and Potential Structural Errors among Indonesian Learners / التشريح النحوي لتركيب الإضافة: دراسة تقابلية وإمكانات الخطأ في البنية التركيبية لدى المتعلمين الإندونيسيين - Yusuf Mamduh; Aisy Binti (IJAS: International Journal of Arabic Studies, 2026)
This study investigates the syntactic structure of the Arabic idāfah construction through a contrastive analysis and examines potential structural errors among Indonesian learners of Arabic. Employing a qualitative descriptive approach, the study analyzes the differences between Arabic and Indonesian syntactic systems and identifies common errors in learners’ use of idāfah constructions. Data were collected through grammatical analysis, learner production, and error classification. The findings reveal significant structural differences between the two languages, particularly in word order, definiteness, grammatical relations, and inflectional patterns. Indonesian learners frequently experience difficulties in arranging the constituents of idāfah, applying the definite article, assigning case endings, and expressing semantic relationships between the two components. The study also indicates that first language transfer and interlanguage development contribute substantially to these errors. The findings highlight the importance of contrastive analysis and error analysis in understanding learners’ difficulties. The study recommends developing instructional materials and teaching strategies that explicitly address the structural differences between Arabic and Indonesian to improve learners’ grammatical competence.